Một số vấn đề lý luận về an sinh xã hội - Thu, Lê Thị Hoài (VNU Journal of Science: Legal Studies; Vol 20 No 1, 2004)
Social security is the way to protect unlucky members of the society through diffirent  methods in order to assist them in case of risk - facing, poverty, sickness, pregnance, woik accident, old-age... Social security enhances the unlucky people get out of thei cirrcumstances.According to the ILO, in Convention No 102 (1952), social security consists of 9 main sectos.In Viet Nam, Social security is a new law-branch, which consists of 3 main parts, th)S( are: social insurance, social assistance, social preference, of which social insurance is hi most important one. In conclusion, the author cofirms that social security-if well managed-wili practical efficiency.